Relevant search with applications for Solr and Elasticsearch - Turnbull, Doug 1980-; Berryman, John 1980- (Manning Publications Co., 2016)
Relevant Search demystifies relevance work. Using Elasticsearch, it teaches you how to return engaging search results to your users, helping you understand and leverage the internals of Lucene-based search engines. About the Technology Users are accustomed to and expect instant, relevant search results. To achieve this, you must master the search engine. Yet for many developers, relevance ranking is mysterious or confusing. About the Book Relevant Search demystifies the subject and shows you that a search engine is a programmable relevance framework. Using Elasticsearch and Solr, it teaches you to express your business's ranking rules in this framework. You'll discover how to program relevance and how to incorporate secondary data sources, taxonomies, text analytics, and personalization. In practice, a relevance framework requires softer skills as well, such as collaborating with stakeholders to discover the right relevance requirements for your business. By the end, you'll be able to achieve a virtuous cycle of provable, measurable relevance improvements over a search product's lifetime. What's Inside Techniques for debugging relevance Applying search engine features to real problems Using the user interface to guide searchers A systematic approach to relevance A business culture focused on improving search About the Reader For developers trying to build smarter search with Elasticsearch or Solr. About the Authors Doug Turnbull is lead relevance consultant at OpenSource Connections, where he frequently speaks and blogs. John Berryman is a data engineer at Eventbrite, where he specializes in recommendations and search.
Includes index. - Online resource; title from title page (Safari, viewed July 26, 2016)
Keywords: Search engines -- Programming; Internet searching; Database searching; Moteurs de recherche; Programmation; Recherche sur Internet; Bases de données; Interrogation; online searching; Search engines; Programming